The material world of digital fictions - Janik , Justyna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
This paper explores the interdependency between digital matter and the representational or mimetic layer of the digital game object. The main aim is to foreground the mechanisms by which the representational elements of the game world emerge from the materiality of the process of play. These mechanisms are examined from the perspective of the ontology of the game object. The issue of digital materiality will be linked with the aesthetical explorations of Tadeusz Kantor, who emphasised the relation between the materiality of the theatre and its fictional elements. As the main example of this analysis, I will focus on Undertale (Toby Fox, 2015) as an example of a game that plays with the boundaries between the fictional world being presented and the elements of digital materiality that are usually hidden from the player’s sight.